Permintaan dan Penawaran Produk Tempe di Kota Makassar, Sulawesi Selatan - Sitti; Aminah; Fatmawati, Siti; Oktavian Hattah, Muhammad Fiqih (Journal Galung Tropika, 2024)
The agricultural sector is vital economic growth; one is by processing agricultural products into valuable products, such as tempeh, from raw soybean materials. The research aims to 1) Describe the characteristics of sellers and buyers of tempeh; 2) Describe the amount of tempeh sold by traders and the amount purchased by consumers; 3) Analyze the factors that affect the demand for tempeh; and 4) Analyze the factors that affect the supply of tempeh. The research was conducted in Pa’baeng-Baeng Market and Terong Market in Makassar City, South Sulawesi. The sample of tempeh traders was 50 people, and the sample of buyers was 200. The analysis methods used were descriptive analysis and multiple linear regression analysis. The results showed that the characteristics of tempeh buyer respondents were 40 years old on average, the average education level was high school (56.82%), the most female gender (83.64%), and predominantly worked as housewives (46.81%). The characteristics of tempeh trader respondents based on age are an average of 41 years, an average high school education level, and the dominant gender is male (74.00%). The average tempeh purchased by consumers is 19 packs/month, and the average tempeh sold is 3,504 packs/month. Simultaneously (F-test) is significant to the demand for tempeh, with a coefficient of determination (R2) of 62.1% that have a significant effect partially (T-test) are all the variables tested, namely the price of tempeh, buyer income, number of family dependents, intensity of need, taste, and price of substitute goods. F-test is significant to the supply of tempeh, with a coefficient of determination (R2) of 60.3%. The significant factor of effect partially (t-test) on the supply of tempeh are the price at the producer level, future price expectations, the number of producers, and the number of consumers. Meanwhile, the price at the trader level is insignificant